Comparative analysis and phylogeny of mitochondrial genomes of Pentatomidae (Hemiptera: Pentatomoidea) - Lian, Dan; Wei, Jiufeng; Chen, Chao; Niu, Minmin; Zhang, Hufang; Zhao, Qing (Frontiers in Genetics, 2022)
The Phyllocephalini is a group of herbivorous insects in Pentatomidae, which lack distinctive morphological characteristics and systematic studies. Up to now, there are only two complete mitochondrial genomes of Phyllocephalini have been reported. In this study, we sequenced and analyzed the complete mitochondrial genomes of three Phyllocephalini species, Gonopsis coccinea, Gonopsimorpha nigrosignata, and Chalcopis glandulosus, which were 16,534, 16,531, and 16,534 bp in length, respectively. The mitochondrial genomes contained 37 genes, including 13 protein-coding genes, two rRNA genes, 22 tRNA genes, and a control region. The gene arrangement was consistent with that of the putative ancestral insect, with no rearrangement. The cox1 gene of Pentatomidae showed the lowest evolutionary rate among the protein-coding genes, the mean genetic distance of species, genera, and subfamilies of Pentatomidae increased hierarchically based on cox1 gene. The 16S rRNA of Pentatomidae was more conserved than 12S rRNA in sequence and secondary structure. All tRNAs could be folded into a typical cloverleaf structure except trnS1. The stem region was more conserved than the loop region in the secondary structure of tRNAs within Pentatomidae. Gonopsis coccinea and Gonopsimorpha nigrosignata had one type of tandem repetition unit in the control region, while C. glandulosus had two types. The heterogeneity analysis of Pentatomidae showed that Phyllocephalinae was the most heterogeneous. Phylogenetic trees based on the newly obtain mitochondrial genomes along with other 50 mitochondrial genomes of Pentatomidae using Bayesian Inference (BI) and Maximum Likelihood (ML) strongly supported the following three relationships: (((Anaxilaus + (Plautia + Glaucias)) + (Nezara + Palomena)) + (Eysarcorini + Carpocorini)), (Hoplistoderini + (Menidini + Asopinae)), and ((Sephelini + Halyini) + (Caystrini + (Cappaeini + (Placosternum + Phyllocephalini)))). The relationships within Phyllocephalini were (Chalcopis + (Dalsira + (Gonopsimorpha + Gonopsis))). Our results provide valuable molecular data for further phylogenetic analyses of Pentatomidae.